2011
DOI: 10.3171/2010.11.jns102148
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa volume increase after surgery for Chiari malformation Type I: a quantitative assessment using magnetic resonance imaging and correlations with the treatment response

Abstract: The treatment response is significantly influenced by the degree of PFV increase, which is dependent on the size of the PF and the extent of the craniectomy, suggesting that the optimal patient-specific PFV increase could be predicted on the basis of preoperative MR imaging and enhancing the perspective that the craniectomy size could be tailored to the individual PFV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 58 publications
1
35
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][65][66][67]70,71,100,[102][103][104][105][106][107][108][109][110][111][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][132]…”
Section: General Informationunclassified
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][65][66][67]70,71,100,[102][103][104][105][106][107][108][109][110][111][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][132]…”
Section: General Informationunclassified
“…Combined series, which included both pediatric and adult patients, constituted 61 reports (42%). [5][6][7]9,11,12,[25][26][27]34,37,38,40,43,44,46,47,52,53,55,63,66,67,70,73,74,76,83,87,90,91,94,96,100,102,103,106,110,111,114,115,117,121,126,127,129,130,132,135,[138][139][140]…”
Section: General Informationmentioning
confidence: 99%
“…1,10 In their series of 11 patients undergoing intradural decompression without duraplasty, Noudel et al measured the increase in posterior fossa volume (PFV) and correlated it with clinical outcomes. 19 They found that the degree of PFV increase positively correlated with symptomatic improvement (p = 0.014). There was a greater in- crease in PFV in patients with a smaller starting volume, and an increase of at least 15% was needed for a complete recovery.…”
Section: Extradural Chiari Decompression Is a Viable And Reproduciblymentioning
confidence: 99%
“…Functional grade was determined using a grading scale previously reported by Noudel et al 19 Patients received an initial postoperative follow-up visit in the clinic between 5 and 40 days (mean 16.27 days), with continual follow-up at several-month intervals thereafter. Clinical improvement was determined by an author who only assessed clinical symptoms and was blinded to the radiological results.…”
Section: Neurological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation